The Self Care Agency pada Pasien Diabetes Mellitus Tipe II di Puskesmas Payung Sekaki Kota Pekanbaru - Wiwik Norlita; Isnaniar; Aufa Denof Utari (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2025)
Diabetes Mellitus is a non-communicable disease (NCD) which is a global health problem and is often not realized by sufferers in the early stages. Diabetes Mellitus occurs due to disturbances in the balance of blood sugar levels, impaired insulin function, abnormalities in pancreatic function in insulin secretion, and concentrated increases in blood sugar levels in the liver with the second highest prevalence globally after hypertension. Objective: This study aims to find out about